1997
DOI: 10.1111/j.1399-3038.1997.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide variations in prevalence of symptoms of allergic rhinoconjunctivitis in children: the International Study of Asthma and Allergies in Childhood (ISAAC)

Abstract: These results suggest substantial worldwide variations in the prevalence and labelling of symptoms of allergic rhinoconjunctivitis which require further study. These differences, if real, may offer important clues to environmental influences on allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
382
7
24

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(437 citation statements)
references
References 13 publications
24
382
7
24
Order By: Relevance
“…Data from the International Study of Asthma and Allergies in Childhood indicate a prevalence of self-reported allergic rhinitis ranging from 0.8% to 14.9% in 6-to 7-year-olds from different centers. 4 The prevalence in all age groups in other studies has ranged from 3% to 19%, 5 perhaps because of differences in definition or aeroallergen prevalence. Allergic rhinitis and asthma commonly occur in the same person.…”
mentioning
confidence: 94%
“…Data from the International Study of Asthma and Allergies in Childhood indicate a prevalence of self-reported allergic rhinitis ranging from 0.8% to 14.9% in 6-to 7-year-olds from different centers. 4 The prevalence in all age groups in other studies has ranged from 3% to 19%, 5 perhaps because of differences in definition or aeroallergen prevalence. Allergic rhinitis and asthma commonly occur in the same person.…”
mentioning
confidence: 94%
“…a llergic rhinitis (AR) is a common nasal disease and affects 10-40% of children with increasing prevalence (1,2). AR frequently coexists with asthma (most studies report a rate of 50-60%) in children (3).…”
mentioning
confidence: 99%
“…[13][14][15][16] The questionnaire also asked about gender, grade, the number of older siblings, shortest distance of residence from one of the six major roads, smoking in the household, and maternal history of asthma, atopic dermatitis, and allergic rhinitis. The six major roads included an expressway, the Meishin Expressway, two national highways, Route 423 and Route 479, and three major Osaka Prefectural roads, the Osaka Central Loop, the OsakaTakatsuki-Kyoto Line, and the Ibaragi-Settsu Line, defined as having maximal daytime traffic volume of 20,000 vehicles or more per 12 hours.…”
Section: Methodsmentioning
confidence: 99%